2015
DOI: 10.1111/1440-1681.12441
|View full text |Cite
|
Sign up to set email alerts
|

Activation of imidazoline‐I3 receptors ameliorates pancreatic damage

Abstract: Agmatine, an endogenous ligand of imidazoline receptors, is reported to exhibit anti-hyperglycaemic and many other effects. It has been established that the imidazoline I3 receptor is involved in insulin secretion. The current study characterizes the role of the imidazoline I3 receptor in the protection of pancreatic islets. The activity effect of agmatine against on streptozotocin (STZ)-induced (5 mmol/L) rat b cell apoptosis was examined by using ApoTox-Glo triplex assay, live/dead cell double staining assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Therefore, multiple effects of KU14R, in addition to the blockade of I‐3R, should be considered. However, with careful application at the effective dose and a suitable target, KU14R can inhibit I‐3R, as described recently . In MIN6 cells, our results demonstrated that KU14R is effective in inhibiting morin at the same dose for the blockade of efaroxan.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Therefore, multiple effects of KU14R, in addition to the blockade of I‐3R, should be considered. However, with careful application at the effective dose and a suitable target, KU14R can inhibit I‐3R, as described recently . In MIN6 cells, our results demonstrated that KU14R is effective in inhibiting morin at the same dose for the blockade of efaroxan.…”
Section: Discussionsupporting
confidence: 79%
“…However, with careful application at the effective dose and a suitable target, KU14R can inhibit I-3R, as described recently. 47,48 In MIN6 cells, our results demonstrated that KU14R is effective in inhibiting morin at the same dose for the blockade of efaroxan. Additionally, KU14R did not enhance insulin secretion directly in MIN6 cells.…”
Section: Discussionmentioning
confidence: 60%
“…Once the concept of imidazoline receptors was accepted by a large number of scientists interested in the potential therapeutic effects and uses of drugs targeting these receptors, they were quickly subdivided into three subtypes: I 1 , I 2 and I 3 . This classification results from biochemical, pharmacological, and functional characterizations (Vauquelin et al, 1999; Morgan and Chan, 2001; Dardonville and Rozas, 2004;Li et al, 2015). This work will also describe the most recent prospects for I 2 and I 3 imidazoline receptors and their possible new clinical applications.…”
Section: History Of Imidazoline Receptorsmentioning
confidence: 96%
“…Imidazoline receptors play important roles in cell proliferation, neuroprotection, inflammation and psychiatric disorders [ 40 ]. Three subtypes of imidazoline receptors have been identified, and all have been reported to contain a binding site for agmatine [ 41 , 42 ]. A previous report suggested that agmatine exerts its neuroprotective effects through a mechanism that involves Nrf2 induction via α2-adrenergic and 5-HT2A receptors in HT22 cells.…”
Section: Discussionmentioning
confidence: 99%